Aspectos legais e éticos na implantodontia - Santos, Pâmela Letícia dos [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia-Júnior, Idelmo Rangel [UNESP] (My University, 2011)
There are few studies that evaluate the legal aspects, consent forms and ethical considerations facing implantology. This paper reviews and discusses the most important criteria in relation to the care of patients needing dental implants. Used the following databases: Medline (Pubmed), Dentistry Oral Science , Scielo, Athenas (Dissertation / Thesis), Digital Library of UNICAMP (Dissertation / Thesis), Digital Library of USP (Dissertation / Thesis) over the past 15 years . The inclusion and exclusion criteria were clinical articles, resulting from expert opinion on the subject of review and longitudinal follow-up who have studied or reported on the ethical aspects in implant dentistry; were excluded studies whose language was not English or Portuguese. Of a total of 52 articles and theses, after an analysis according to inclusion and exclusion criteria, 26 were selected. The literature shows that the safe practice of implantology is indispensable for the success of therapy. Respect the ethical, legal and make it explicit relationship with the patient (informed consent, information) are an important factor in the success of rehabilitative treatment. Since this treatment is long term, professional dental implant requires all documentation and clarity in time to offer treatment to the patient and professional expectations are met.

Existem poucos estudos na literatura que avaliam os aspectos legais, termos de consentimento e considerações éticas voltados para o Implantodontista. O presente estudo revisa e discute os critérios mais importantes com relação ao atendimento dos pacientes que necessitam de implantes osseointegráveis. Foram utilizadas as seguintes bases de dados: Medline (Pubmed), Dentistry Ora Science, Scielo, Base Athenas (Dissertação/Teses), Biblioteca Digital da Unicamp (Dissertação/Teses), Biblioteca Digital da USP (Dissertação/Teses) nos últimos 15 anos. Os critérios de inclusão e exclusão foram: artigos clínicos, resultantes de opinião de especialistas no assunto, de revisão e longitudinais de acompanhamento que estudaram ou relataram sobre os aspectos éticos na Implantodontia; foram excluídos estudos cujo idioma não fosse o inglês ou o português. De um total de 52 artigos e teses, após uma análise, segundo o critério de inclusão e exclusão, foram selecionados 26. A literatura demonstra que a prática segura da Implantodontia é indispensável para o sucesso da terapia. Respeitar os aspectos éticos, legais e tornar o relacionamento sempre muito claro com o paciente (termo de consentimento, informações adicionais) são vertentes importantes para o sucesso do tratamento reabilitador. Uma vez que, este tratamento é em longo prazo, a Implantodontia exige do profissional toda documentação e, clareza no momento de oferecer o tratamento, para que as expectativas do paciente e profissional sejam atingidas.
Legal and ethical aspects in implantology
Keywords: Dental implant; Ethics dental; Legislation dental; Implante dentário; Ética dental; Legislação odontológica